Association of marital status with DNA methylation-based biological age among US older adults - Cui, Xian; Huo, Jianghua; Xu, Yaqian; Zhang, Hui; Ding, Chongyu; Du, Jun; Li, Xiangwei (Frontiers in Public Health, 2025)
BackgroundDNA methylation (DNAm) algorithms, such as GrimAge and GrimAge2, have emerged as reliable measures of biological age acceleration and may offer additional insights into health outcomes. While previous research has explored the relationship between marital status and mortality, its association with accelerated biological aging remains understudied. This study aimed to examine the relationship between marital status and DNAm-based biological age acceleration in older adults.MethodsData from the National Health and Nutrition Examination Survey (NHANES) were used to assess GrimAge and GrimAge2 in 2,420 U.S. adults aged 50 and older. DNAm profiles were measured using the Infinium Methylation EPIC BeadChip kit (Illumina). Linear regression models, adjusted for potential confounders, were used to estimate associations between marital status and DNAm-based biological age acceleration.ResultsSignificant associations were observed between marital status and biological age acceleration. After adjusting for potential confounders, never-married males had significantly higher GrimAge2Acc (β = 0.95, 95% CI: 0.17–1.73) and GrimAgeAcc (β = 0.88, 95% CI: 0.28–1.47) scores compared to married males. Additionally, widowed females exhibited significantly higher GrimAge2Acc (β = 0.43, 95% CI: 0.02–0.85) compared to their married counterparts.InterpretationThis study highlights the significant role of marital status in biological aging, particularly for men. Never-married status may be linked to higher risks of biological aging, highlighting the need for social and environmental interventions that promote healthier lifestyles and emotional support for older adults, especially those without partners. These findings underscore the importance of addressing social determinants of health to mitigate the adverse effects of marital status on biological aging and overall health outcomes.